The use of portable OSL and IRSL measurements of NaCl in low dose assessments following a radiological or nuclear emergency - Alghamdi, Hamdan; Sanderson, David; Carmichael, Lorna; Cresswell, Alan; Martin, L. (Frontiers in Public Health, 2022)
During recovery phases following a nuclear or radiological incident analyses of doses received by members of the public and responders are often required. Several methods have been investigated for use at different timescales after the incident, including assessments based on measurements of materials present at the time of the incident. Common salt has previously been shown to have potential for retrospective dosimetry in the mGy dose range using laboratory instrumentation. This preliminary study investigates the use of portable instruments, with unprepared commercially sourced salt, in dose ranges below 100µGy. Responses from pulsed IRSL and portable OSL instruments were compared. For OSL measurements, detection limits of 7µGy have been demonstrated, with detection limits of 30-340µGy for the other instruments investigated. Dose responses in the 0-500µGy range were determined for the most sensitive systems, which show a linear response over this dose range with a non-zero intercept representing doses received from environmental sources since manufacture of the salt. For use as a dosimeter, methods of removing or accounting for inherited signals will be required in this low dose range. The results demonstrate that salt has considerable potential for use in retrospective dosimetry below 100µGy, and that measurements can be conducted with portable OSL instruments.